A novel protein CtCBP-1 functions as a crucial macromolecule during mineralization of limpet teeth - Wang, Yadong; Zhang, Rongqing; Liu, Chuang (Frontiers in Marine Science, 2022)
Limpets are a class of marine mollusks that use mineralized teeth, one of the hardest and strongest biological materials, to feed on algae on rocks. By combining proteomics and RNA-seq analysis of limpet radula, we identified a novel chitin-binding protein (CtCBP-1) that may play a regulatory role in radula mineralization of Cellana toreuma. In this study, the full-length cDNA of CtCBP-1 gene was cloned for the first time, and the protein was successfully expressed in vitro. In vitro experiments demonstrated that CtCBP-1 binds well to both goethite and chitin, which are key components of the cusp. We studied the function of CtCBP-1 on goethite crystallization in vitro, revealing that it changed the morphology of goethite crystals. We also used fluorescence higher resolution imaging to map the binding of CtCBP-1 in radula and found that the distribution of CtCBP-1 on radula was specific, which consistent with the SEM results finding tightly aligned goethite. In this study, a novel protein CtCBP-1, which regulates the distinctive biomineralization process of limpet teeth, is identified for the first time. This protein’s identification may inform biomimetic techniques for creating hard materials that can withstand ambient temperature.